ANALISIS PERSEDIAAN BAHAN BAKU KAYU SENGON LAUT (Paraserianthes falcataria (L.) Nielsen) UNTUK MENUNJANG KELANCARAN PRODUKSI PLYWOOD DI PT SURYA SATRYA TIMUR CORPORATION BANJARMASIN - Muhamad Heri Ende Adil; Noor Mirad Sari; Adi Rahmadi (Universitas Lambung Mangkurat, 2020)
This study aims to find out and analyze the estimated use of raw materials for sengon laut wood in the manufacture of plywood, determine the number of orders of economical raw materials, find out the time of reorder and find out the amount of safety supplies at PT Surya Satrya Timur Banjarmasin Corporation. The benefits of this research can be used as a source of reference for companies in analyzing a production management activity, especially controlling raw material inventories. Data is generated through interviews and field observations which then data is processed using the moving average method to analyze the estimated raw material use in 2019 and use the Economic Order Quantity (EOQ) method to analyze economic raw material processing. Based on the calculation results it is known that the raw material needed for 2019 is 24,419,750 m3 with the optimum number of orders as much as 45 times with a total raw material of 541,781 m3 in one message. The amount of safety supplies provided by the company is 238,482 m3 with the point of reorder when the raw materials are left with 485,979 m3. The warehouse capacity is enough to provide raw materials as much as 780,265 m3 to avoid running out of raw materials and avoiding waste of raw materials. Thus the availability of raw materials will facilitate an economical and efficient production process.Keywords: Inventory Control; Raw Materials; Plywood; EOQ